The effect of service quality on customer satisfaction in digital age: customer satisfaction based examination of digital CRM - Demirel, Demokaan (Journal of Business Economics and Management, 2022)
This study examines how customer-centered management systems contribute to CRM through the use of digital services. The article presents empirical evidence from an online survey of 405 people using digital services living Kocaeli province in Turkey and modelling a system of structural equations using partial least squares. 405 people have been selected by a random sampling method to ensure objectivity and scientific neutrality. Among the 405 people, 350 were found to have filled out the questionnaire completely. The study also examined the relationship between the dimensions of service quality and customer satisfaction. The results confirm that most of the dimensions of digital service quality favour the development of customer satisfaction capabilities and both the relationship the independent variables and trust, Enthusiasm, and sensitivity dimensions and customer satisfaction are positive. High customer satisfaction with digital services can lead to superior firm performance; however, companies should also gain credibility for customers and should design their products according to customer preferences. First published online 23 February 2022